Effects of maturation stage on sprinting speed adaptations to plyometric jump training in youth male team sports players - Silva, Ana Filipa (2022)
Purpose: To determine the effects of maturation stage (eg, classified in the same intervention protocol as early-, and late-mature) on linear sprinting speed adaptations to plyometric jump training (PJT) in youth (aged <18 years) male team sports players. Patients and Methods: Eligibility criteria was determined based on PICOS: (P) healthy youth male team sport players classified in the same intervention protocol in ≥2 maturation-related categories, based on a recognized maturation stage-determination method, including (but not limited to) Tanner stage; peak height velocity (eg, Mirwald method); radiography-based method (eg, Fels method); (I) athletes exposed to PJT with a minimum of 4 weeks duration; (C) athletes non-exposed to PJT (non-dedicated intervention, ie, only field-based regular training) or performing a parallel intervention not-related with PJT organized by maturation levels; (O) sprinting speed (eg, time, maximal sprint speed) measured in any linear sprint test trajectories before and after the intervention; (S) only randomized controlled and/or parallel trials. Searches were conducted on December 2021 in EMBASE, PubMed, Scopus, SPORTDiscus and Web of Science, restricted to Portuguese, Spanish and English languages, with no restrictions regarding publication date, and no filters applied. The PEDro scale was used to assess the risk of bias in the included studies. Meta-analysis was computed using the inverse variance random-effects model. The significance level was set at p < 0.05. Results: The search identified 1219 titles. From those, four studies were selected for qualitative and quantitative synthesis. Four studies provided data for sprinting performance, involving 10 experimental and 8 control groups showing a small effect of trained participants on sprinting performance (ES = 0.31; p = 0.064; I2 = 41.3%) when compared to controls. No significant moderator effect was noted for somatic maturity (p = 0.473 between groups). Conclusion: PJT had no significant effect on sprinting performance, although the inclusion criteria partially may explain that.